RELATIONSHIP OF THE NATIONAL ASSEMBLY WITH THE EXECUTIVE AND JUDICIAL POWERS - Manukyan, Martin (State and Law, 2025)
This article talks about the relationship of the National Assembly with the executive and judicial powers. The author came to the conclusion that under the parliamentary model, the functions performed by the state authorities are actually not equal in nature and differ from each other in legal force and content, that is, the activities of the legislative branch are of a legislative nature, and the judicial and executive authorities are of a sub-legislative nature. The article also emphasizes the idea that the legislative branch has so-called “functional superiority” over other branches of government, which in itself should not be considered as a violation of the constitutional balance between the legislative, executive and judicial branches of government. Because the essence of the principle of separation and balancing of powers is not to preserve equal functions for the branches of government, which, due to the nature of the functions of the branches of government, are no longer equal, but to ensure the necessary and sufficient powers of each branch of government.Addressing the issue that one of the central issues in the relationship between the branches of legislative and executive power is parliamentary control over the executive power, and emphasizing that in such conditions it is necessary to ensure effective mechanisms to curb the dominance of the executive power (Prime Minister) becomes of key importance, the author as a political guarantee of the implementation of high-quality control in relation to the executive branch, it takes into account the presence of a strong parliamentary opposition, because the main criterion for creating an opposition is not power, law, but the limitation of power by law.